Arterial stiffness is associated independently with liver stiffness in biopsy-proven nonalcoholic fatty liver disease: a transient elastography study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Background Nonalcoholic fatty liver disease (NAFLD) has been associated with an increased arterial stiffness. However, the question as to whether an association exists between the extent of vascular and liver stiffness in patients with biopsy-proven NAFLD remains open. In this study, we sought to investigate whether pulse wave velocity (PWV) and augmentation index (AIx) - two common indices of arterial stiffness - are associated with (a) liver stiffness measurement (LSM) on transient elastography (TE) and (b) histological liver fibrosis. Patients and methods We examined 125 patients with biopsy-proven NAFLD and 55 age-matched and sex-matched controls. Arterial stiffness of the brachial artery was measured using a Mobil-O-Graph arteriography system. LSM was assessed using TE, whereas the presence of advanced fibrosis (F >= 3) was determined on histology. Results Patients with NAFLD had higher PWV [median: 7.2 (6.3-8.2) and 6.2 (5.5-6.7) m/s, respectively,P < 0.001] and AIx (mean: 21.3 +/- 13.5 and 17.2 +/- 11.9%, respectively,P=0.01) compared with the controls. LSM showed positive correlations with both PWV (rho = 0.300;P<0.01) and AIx (rho = 0.223,P = 0.02). Both indices of arterial stiffness were higher in patients with advanced fibrosis than in those with nonadvanced fibrosis (F <= 2). Conclusion The severity of arterial and liver stiffness increases in parallel in patients with biopsy-proven NAFLD. Systematic risk assessment for reducing arterial stiffness is recommended in the presence of TE-determined advanced fibrosis.
Keywords: arterial stiffness; Fibroscan; fibrosis; liver stiffness; nonalcoholic fatty liver disease; transient elastography; HEPATIC-FIBROSIS; CARDIOVASCULAR EVENTS; MORTALITY; DIAGNOSIS; TESTS; RISK